A generic theory of change-based framework with core indicators for monitoring the effectiveness of large-scale food fortification programs in low- and middle-income countries - Rodas-Moya, Santiago; Giudici, Francesca M.; Owolabi, Adedotun; Samuel, Folake; Kodish, Stephen; Lachat, Carl; Abreu, Taymara; van het Hof, Karin; Osendarp, Saskia; Brouwer, Inge D.; Feskens, Edith; Melse-Boonstra, Alida (Frontiers Media, 2023)
Large-scale food fortification (LSFF) programs are widely implemented in low- and middle-income countries (LMIC) to alleviate micronutrient deficiencies. However, these programs may not achieve the desired impact due to poor design or bottlenecks in program implementation. Monitoring and evaluation (M&E) frameworks and a set of agreed indicators can help to benchmark progress and to strengthen the evidence-base of effectiveness in a standardized way. We aimed to formulate recommendations towards core indicators for evaluating the effectiveness of LSFF programs with their associated metrics, methods, and tools (IMMT). For this, we used a multi-method iterative approach, including a mapping review of the literature, semi-structured interviews with international experts, compilation of a generic Theory of Change (ToC) framework for LSFF program delivery, and selection of IMMT for M&E of LSFF programs at key stages along the ToC delivery framework. Lastly, we conducted exploratory, qualitative interviews with key informants in Nigeria to explore experiences and perceptions related to the implementation of LSFF programs in Nigeria’s context, and their opinion towards the proposed set of core IMMT. The literature search resulted in 14 published and 15 grey literature documents, from which we extracted a total of 41 indicators. Based on the available literature and interviews with international experts, we mapped a ToC delivery framework and selected nine core indicators at the output, outcome and impact level for M&E of the effectiveness of LSFF programs. Key informants in Nigeria revealed that the main bottlenecks for implementation of the proposed IMMT are related to the lack of technical capacity, equipment, laboratory infrastructure, and financial resources. In conclusion, we propose a set of nine core indicators for enabling comprehensive M&E of the effectiveness of LSFF programs in LMIC. This proposed set of core indicators can be used for further evaluation, harmonization and integration in national and international protocols for M&E of LSFF programs.